Content Vol. 42 No. 3 (2021) - Editorial, Coordinador (Revista Mexicana de Ingenieria Biomedica, 2021)
E-book edition of the volume 42, number 3, year 2021, of the Revista Mexicana de Ingeniería Biomédica. In this issue: A Practical Review of the Biomechanical Parameters Commonly Used in the Assessment of Human Gait Image-based Glaucoma Classification Using Fundus Images and Deep Learning Identification of 7 Movements of the Human Hand Using sEMG - 360° on the Forearm The Shielding Volume Reduction in a High Dose Rate Brachytherapy Room